1965
DOI: 10.1128/am.13.5.776-780.1965
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Chlorine Dioxide as a Bactericide

Abstract: We found chlorine dioxide to be a more effective disinfectant than chlorine in sewage effluent at p H 8.5. Chlorine dioxide was also found to be a more stable bactericide in relation to p H in the range studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(22 citation statements)
references
References 4 publications
(1 reference statement)
0
15
0
1
Order By: Relevance
“…It was suggested [57] that the effectiveness of chlorine dioxide is due to its adsorption by the cell wall, where chlorine dioxide reacts with enzymes containing sulfhydryl groups. In contrast, it was shown [58] that chlorine dioxide inhibits protein synthesis. Although both experiments were performed in bacterial cells, chlorine dioxide is likely to interact with phototrophic microorganisms similarly.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It was suggested [57] that the effectiveness of chlorine dioxide is due to its adsorption by the cell wall, where chlorine dioxide reacts with enzymes containing sulfhydryl groups. In contrast, it was shown [58] that chlorine dioxide inhibits protein synthesis. Although both experiments were performed in bacterial cells, chlorine dioxide is likely to interact with phototrophic microorganisms similarly.…”
Section: Discussionmentioning
confidence: 92%
“…The effects of chlorine dioxide depend on the solution concentration, the presence of organic matter, pH and temperature. Depending on the chlorine dioxide concentration and the length of exposure, a 7-30% reduction of microorganisms can occur within 1 h [58]. It was found [59] that a 0.25 mg/L solution of chlorine dioxide inactivated a strain of E. coli in less than 60 s at pH 6.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTWS is an HLD procedure that uses ClO 2 , whose efficacy in terms of decontamination has been well known since the 60s [17,18]. Over the years, in-vitro and pre-clinical studies reported equal or greater bactericidal, mycobactericidal and sporicidal activities than traditional disinfectants in terms of viable count reduction and time needed to reach the HLD standard [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The bactericidal effect of ClO 2 has been known for more than a century and has been demonstrated many times over the years, 19–23 however, it is not fully understood how ClO 2 inactivates pathogens. Previous research has shown that the reaction of chlorine dioxide leads to leakage of endo -plasmatic matter, which indicates membrane damage in E. coli .…”
Section: Introductionmentioning
confidence: 99%